Trophic Niche and Diversity of a Pelagic Squid (Dosidicus gigas): A Comparative Study Using Stable Isotope, Fatty Acid, and Feeding Apparatuses Morphology - Gong, Yi; Li, Yunkai; Chen, Xinjun; Yu, Wei (Frontiers in Marine Science, 2020)
Commercially important pelagic squid such as jumbo squid Dosidicus gigas play a key role in energy and nutrient transfer in marine ecosystem. Geographic variations in the foraging strategy of D. gigas can provide valuable information on cephalopod trophic diversification and adaption to natural and anthropogenic impacts. Here, we used a novel combination of stable isotope (SI) and fatty acid (FA) analyses of muscle tissues and morphometric measurements of feeding apparatuses to evaluate spatial patterns of habitat and resource use of D. gigas collected from three main fishing grounds in the tropical and southern temperate Pacific Ocean. Results showed that the δ13C and δ15N values were different among geographic stocks within D. gigas, possibly because of site-specific dietary sources and isotopic baseline values. Spatial variabilities in FA profiles/biomarkers, combined with SI results, suggests two foraging patterns: utilization of resources mainly from oceanic food webs or from both neritic and oceanic food webs. This behavior likely promotes the site-specific trophic niche width, increases adaptation to inhabiting oceanographic conditions, and could be driven by differences in feeding apparatuses morphology, body size, and trophic position. These results emphasize the dietary flexibility of D. gigas and their important ecological roles in ecosystems as cross-biome trophic linkages. Trophic diversification of pelagic squid like D. gigas may have important implications for their population dynamics, ecological associations, and subsequent management.